Intimidades enclaustradas: sexualidad y moral. Entrevista con Asunción Lavrin (Guanajuato, Mexico, agosto 2011) - Rafael Castañeda García (Centre de Recherches sur les Mondes Américains, 2012)
The interview to Asunción Lavrin is about his intellectual trajectory. This paper details how she became interested in the issue of women's history in Latin America, and the importance of studying the manuscripts of nuns as a way of understanding women's spirituality. The historian defines key concepts such as sexuality, gender and masculinity, highlights the fact that generic studies to include men and women. It also explains the relevance of the study of children in secular and religious level. In the last part indicates the multiple sources that exist today for a twentieth-century history, the need for dialogue with other disciplines and to approach the cultural history.